IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MI ROUDLOTUL JANNAH BOROJABUNG MALANG - Restu Hermin Aprilliawati; Ika Ratih Sulistiani; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Schools act as educational institutions that have a complex and dynamic system, where the government launched an educational autonomy policy which we know is MBS (School-Based Management) which is a form of participation from the community for the world of education. One example of an educational institution that implements SBM (School-Based Management) is MI Roudlotul Jannah Borojabung in Jabung village. The purpose of this study was to determine the planning, implementation and results of School-Based Management in Improving the Quality of Education at MI Roudlotul Jannah Borojabung Malang. The method used in this research is a qualitative approach with the type of case study research. For data collection techniques, researchers collected data through observation, interviews, and documentation techniques. Meanwhile, to check and examine data from various data collection techniques and existing data sources, researchers used data triangulation techniques. The results of the implementation of school-based management in improving the quality of education at MI Roudlotul Jannah Borojabung Malang seen in the 3 national education standards can be said to be quite successful, the three standards can be implemented better and more optimally thanks to the implementation of SBM, which this also results in increased achievement both from students, teachers, and also schools and school education goals can be achieved. Although there are several aspects that need to be addressed, such as the division of subjects that must be taught by the teacher, one teacher should teach 1 subject so that it can be implemented optimally. Keyword: School-Based Management, Quality of Education, Qualitative Research.